Decompression vs. Decomposition: Distribution, Amount, and Gas Composition of Bubbles in Stranded Marine Mammals - Bernaldo de Quirós, Yara; González-Díaz, Óscar; Arbelo, Manuel; Sierra, Eva; Sacchini, Simona; Fernández, Antonio (Frontiers in Physiology, 2012)
"Gas Bubble Disease" or “Decompression-like Sickness" was described in stranded beaked whales linked to military sonar. Findings of gas bubble presence or associated lesions in marine mammals have been reported more and more often during the last decade. These descriptions suggest that gas bubbles in marine mammal tissues may be more common than previously thought. In this study we have analyzed gas amount (by gas score) and compositiones and within different decomposition codes following a standardized methodology. This broad study has allowed us to explore species-specific variability in the bubble’s prevalence, distribution and composition , as well as masking by putrefaction gases. We found that the presence of bubbles detected within the cardiovascular system and tissues during the necropsy of stranded cetaceans is a common finding related to “in vivo and / or postmortem” process. To try to avoid masking by putrefaction gases, necropsy and gas sampling must be performed as soon as possible, before 24 hours post mortem is recommended but preferably within 12 hours post mortem. At necropsy, quantity of bubbles (gas score) in decomposition code 2 in stranded cetaceans was found to be more important than the merely presence versus absence of bubbles. Deep divers presented higher abundance of gas bubbles mainly composed of 70% nitrogen and 30% CO2, suggesting a higher predisposition of these species to suffer from decompression.